Lighting conditions at study areas in academic library : enhancement to the learning environments / Haris Hambali ... [et al.] - Hambali, Haris; Sufar, Suhaila; Talib, Anuar; Abd. Aziz, Mohd. Nizam (2012)
The library is the heart of academic buildings community especially in higher education institutions, colleges and schools. It should be designed not only to meet the requirements of good facilities, physical aspect of the environment such as lighting, temperature, humidity and the acoustic space that contribute to the student’s learning activities but also its reference materials. Studies revealed that the physical environment in interior library did contribute to the positivity of student learning especially through reading and writing which the most common activities. Thus, the suitable lighting illuminance should be designed according to the Standard guideline. The objective of this paper is to measure the illuminance levels (lux) of the existing lighting conditions in the library by comparing between the Malaysian Standards of MS ISO 8995:2005 Lighting of Indoor Workplace, JKR and PERPUN Standards (Malaysian University Libraries Association) and will be conducted in four (4) different study spaces namely Open Study Space, Individual Carrel, Discussion Room and Leisure Reading Area in three (2) case studies in Perak State. The results can be applied to improve the lighting conditions for the better library environment and as the outcomes and benefits, it can be applied and will help in improving the conduciveness of current and future physical environments of the academic libraries in Malaysia as a place for learning and scholarship activities.